(untitled) (Advances in Knowledge Representation, 2023)
The difficulty of classical accounting in measuring intangible assets promoted the emergence of a thematic is called Intellectual Capital Accounting. However, the change from the classic format to a new one results in the need towards identifying aspects that support this discussion. In this context, this research aims to identify aspects that underlie Intellectual Capital Accounting. Through a qualitative approach, of an exploratory-descriptive nature, this research made use of Content Analysis as a method for treating the ambitioned. As a result, this thematic sustain itself by aspects related to the clash between classic accounting and the one oriented to intangible assets, with management aspects inherent to the organizational strategy, value creation, knowledge and other organizational resources, with a view to measurement and better organizational performance. The expansion of this investigation to other bases, as well as obtaining the perception of experts in relation to other aspects, are suggestions for future research.